Comparing government redistribution across countries: The problem of second-order effects - David K. Jesuit; Vincent A. Mahler (Luxembourg Income Study (LIS), 2010)
The traditional way of measuring government redistribution across countries is to compare the income households report that they receive from private sources with the income they receive after government transfers have been added and taxes and social insurance contributions deducted. Unfortunately, this conventional measure does not capture 'second order' effects whereby income guarantees arising from public pensions make it less necessary for people to save for their retirement, rendering the 'pre-government' counterfactual to the observed post-government distribution unrealistic. In addressing this problem, we offer an alternative to the conventional direct redistribution measure that considers claims to future income generated by both the public and the private sectors. Data have been calculated for 51 country-years from household income surveys available from the Luxembourg Income Study.
Keywords: 330; Verteilungspolitik; Einkommensumverteilung; Messung; Gini-Koeffizient; OECD-Staaten